Behaviour change physiotherapy intervention to increase physical activity following hip and knee replacement (PEP-TALK): study protocol for a pragmatic randomised controlled trial. Issue 7 (19th July 2020) - Smith, Toby O; Parsons, Scott; Fordham, Beth; Ooms, Alexander; Dutton, Susan; Hing, Caroline; Barber, Vicki S; Png, May Ee; Lamb, Sarah
Abstract : Introduction: While total hip replacement (THR) and total knee replacement (TKR) successfully reduce pain associated with chronic joint pathology, this infrequently translates into increased physical activity. This is a challenge given that over 50% of individuals who undergo these operations are physically inactive and have medical comorbidities such as hypertension, heart disease, diabetes and depression. The impact of these diseases can be reduced with physical activity. This trial aims to investigate the effectiveness of a behaviour change physiotherapy intervention to increase physical activity compared with usual rehabilitation after THR or TKR. Methods and analysis: The PEP-TALK trial is a multicentre, open-labelled, pragmatic randomised controlled trial. 260 adults who are scheduled to undergo a primary unilateral THR or TKR and are moderately inactive or inactive, with comorbidities, will be recruited across eight sites in England. They will be randomised post-surgery, prior to hospital discharge, to either six, 30 min weekly group-based exercise sessions (control), or the same six weekly, group-based, exercise sessions each preceded by a 30 min cognitive behaviour approach discussion group. Participants will be followed-up to 12 months by postal questionnaire. The primary outcome is the University of California, Los Angeles (UCLA) Physical Activity Score at 12 months. Secondary outcomes include: physical function, disability, health-related quality of life, kinesiophobia, perceived pain, self-efficacy and health resource utilisation. Ethics and dissemination: Research ethics committee approval was granted by the NRES Committee South Central (Oxford B - 18/SC/0423). Dissemination of results will be through peer-reviewed, scientific journals and conference presentations. Trial registration number: ISRCTN29770908 .